2007
DOI: 10.1007/s11517-007-0267-x
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effects of a controllable knee ankle foot orthosis for functional compensation of gait in patients with proximal leg weakness

Abstract: Application of intermittent control of the knee joint stiffness in a knee ankle foot orthosis (KAFO) during gait is proposed. The approach combines inertial sensors and an actuator system in order to apply compensation in quadriceps weakness with a wearable device. Two methods, segment-angular rotation based and segment-angular velocity based, are analysed for the control of the knee joint state (intermittent stiffness) based on the inertial sensors signals. Protocolled tests are developed with two post-polio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 19 publications
1
26
0
1
Order By: Relevance
“…We were able to confirm these compensatory movements in our sample when walking with the orthosis in the locked mode. However, when walking with the SCO with the knee joint unlocked, we found an average knee swing flexion angle of 57°±15°, which is in line with the results of previous studies that found knee swing flexion angles between 29° and 65° across their subject samples [6,41,[43][44][45][46]. Physiologically, sound humans walk with a knee flexion angle of about 65° between 40-75% of the gait cycle, representing an important contributor to sufficient toe clearance of the swinging leg [47,48].…”
Section: E-mag Locked E-mag Unlocked Significantsupporting
confidence: 91%
“…We were able to confirm these compensatory movements in our sample when walking with the orthosis in the locked mode. However, when walking with the SCO with the knee joint unlocked, we found an average knee swing flexion angle of 57°±15°, which is in line with the results of previous studies that found knee swing flexion angles between 29° and 65° across their subject samples [6,41,[43][44][45][46]. Physiologically, sound humans walk with a knee flexion angle of about 65° between 40-75% of the gait cycle, representing an important contributor to sufficient toe clearance of the swinging leg [47,48].…”
Section: E-mag Locked E-mag Unlocked Significantsupporting
confidence: 91%
“…El Grupo de Neuro-Rehabilitación del Instituto Cajal ha sido uno de los pioneros a nivel mundial en este tipo de tecnologías. Los primeros desarrollos, en el marco del proyecto europeo GAIT, se centraron en exoesqueletos unilaterales de miembro inferior, dirigidos, por tanto, a trastornos neurológicos como el ictus, y con el objetivo de normalizar y rehabilitar el patrón de marcha patológico (Moreno et al, 2008;Cullell et al, 2007). Las aportaciones en este ámbito se han centrado en el desarrollo de nuevos actuadores compactos y energéticamente eficientes (Moreno et al, 2005;Claros et al, 2016) y en el desarrollo de sistemas sensoriales, tanto para la segmentación del ciclo de la marcha, como para la identificación de estados y sub-fases de dicho ciclo (Moreno et al, 2006;Lambrecht et al, 2016).…”
Section: Robótica De Rehabilitación Y Asistenciaunclassified
“…Stance-control orthoses (SCOs) are lower-limb assistive devices that prevent knee collapse during weightbearing while allowing free knee motion during the swing phase of gait [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The methods of controlling and applying knee-flexion resistance, device complexity, device function, and user acceptance vary considerably between stance-control devices.…”
Section: Introductionmentioning
confidence: 99%
“…Another orthosis used inertial, angular-position, and force sensors in a custom actuator system to apply varying stiffness to an orthosis knee joint [10]. Since the system used predetermined relationships between resisting torque and joint angle to switch between stance and swing modes, the device may not handle unexpected conditions such as stumbling.…”
Section: Introductionmentioning
confidence: 99%